Comparison of [99mTc]Tc-FAPI SPECT/CT and [18F]FDG PET/CT as predictive biomarkers for immunotherapy response in gastrointestinal cancer - Yu Zhang; Hong Chen; Dajia Lin; Zhiyi Lin; Jiyun Shi; Hannan Gao; Chenshen Huang; Fangqing Xue; Fan Wang; Wenxin Chen (Scientific Reports)
Abstract To explore the diagnostic performance of [99mTc]Tc-FAPI SPECT/CT for gastrointestinal cancer, compared to [18F]FDG PET/CT. In this analysis of a prospective trial, consecutively recruited patients from a single center with pathologically confirmed gastrointestinal cancer were prospectively enrolled from September 2022 to June 2024 and underwent paired v and [18F]FDG PET/CT examinations at intervals of more than 1 day and within 7 days of each other.The activity of tracer accumulation in lesions was assessed by maximum standardized uptake value(SUVmax) and TBR (lesions SUVmax/ascending aorta SUVmean). Histopathologic and clinical follow-up results were used as reference standards for final diagnoses. Seventy-eight patients (46 men; median age, 58.8 ± 14.5 years) were evaluated. Compared with the TBR for [18F]FDG uptake, TBR for [99mTc]Tc-FAPI uptake was higher in primary tumor(4.6 ± 2.0 vs. 3.4 ± 1.7; P = 0.001) ,peritoneal spread (1.3 [1.1,7.3] vs. 1.1[1.1,1.1]; P = 0.001 ) and liver metastases( 2.5[1.1,8.5] vs. 1.1[1.1,3.4]; P = 0.031). For diagnostic accuracy in a total of 253 lesions in 78 patients, compared with [18F]FDG PET/CT, [99mTc]Tc-FAPI SPECT/CT demonstrated a higher sensitivity (100% [15 of 15 lesions] vs. 20% [3 of 15]; P < 0.001), accuracy (100% [48 of 48 lesions] vs. 75% [36 of 48];P < 0.001), and negative predictive value (100% [33 of 33 lesions] vs. 69% [36 of 48 lesions]; P = 0 0.001) in detecting peritoneal spread, and a higher sensitivity (85% [17 of 20 lesions] vs. 50% [10 of 20]; P = 0.041) in detecting liver metastases. Patients with metastatic gastrointestinal carcinomas negative on the [99mTc]Tc-FAPI scan showed improved clinical prognosis after immunotherapy (P<0.006). TBR-FDG/TBR-FAPI was the main predictor of better prognosis post-immunotherapy ([stable disease, SD]+[partial response, PR]), with an optimal cut-off of 3.82. [99mTc]Tc-FAPI SPECT/CT can better evaluate peritoneal spread and liver metastases in gastrointestinal cancer. Furthermore, TBR-FDG/TBR-FAPI is a valuable imaging parameter for monitoring immunotherapy responses.